Clinical outcomes up-to 10 years of asymptomatic incidental aortic dissections and large aortic aneurysms detected on computer tomography aortography (CTA) prior to transcatheter aortic valve implantation (TAVI). (14th October 2021) - Tan, J H; Teoh, T K; Fong, J; Amirthalingam, A; Baig, K
Abstract: Background/Introduction: Computer tomography aortography (CTA) is performed routinely to aid planning of transcatheter aortic valve implantation (TAVI). Incidental findings are common, and may influence the decision to proceed with TAVI. The safety and long term outcomes of performing TAVI in patients with previously undiagnosed incidental CT findings of aortic dissections and large aortic aneurysms is currently unknown. Purpose: To establish the frequency of incidental aortic dissections and large aortic aneurysms prior to TAVI, and subsequent clinical outcomes of patients. We hypothesize that transfemoral access is safe in patients with incidental finding of aortic dissection and large aortic aneurysms. Methods: This was a retrospective study of 628 sequential TAVI patients in a large, UK tertiary centre between January 2010 and September 2020. Patients were evaluated in 3 groups as per pre-TAVI CTA: incidental aortic dissections, aortic aneurysm >4cm and all others (control group). Endpoints were procedural success, peri-procedural major bleeding and/or vascular complications and/or CVA, length of hospital stay, 30-day and 1-year mortality. Results: 2.9% of patients (n=18) had incidental aortic dissection, of which 66.7% (n=12) were male, with a mean age of 86.7±4.4. 3.8% of patients (n=24) had aortic aneurysms >4 cm. 83.3% (n=20) of them were male and the mean age was 82.8±5.4. Transfemoral approach was favoured in 77.8% of patients in the dissection group and 83.3% of patients in the aneurysm group versus 93.3% in the control group. Procedural characteristics are summarised in Table 1. Vascular access complications, stroke, bleeding and length of hospital stay were comparable between all 3 groups (Table 1). Patients with dissection and large aneurysm had similar success rate of valve implantation compared to the control group (88.9% and 87.5% vs 97.1%, p=0.452). 30-day mortality in the dissection group was higher than the other 2 groups (21.1% vs 0% and 5.6%, p=0.004). Log-rank analysis revealed a higher incidence of MACE in the dissection group over 24 months compared to the other two groups (Figure 1). Conclusion: A transfemoral approach appears to be a safe choice in patients with incidental findings of aortic dissection or aortic aneurysms >4cm, given no significant difference in terms of valve implant success, vascular injury, major bleeding or unplanned surgical repair. However, patients with stable previous aortic dissections have a significantly higher 30-day mortality and overall lower survival rate over 24 months. This important observation needs to be further investigated in a larger-scale, long-term follow up study, and may in future influence TAVI treatment planning. FUNDunding Acknowledgement: Type of funding sources: None.